K původu civilismu. Několik exegezí nejen neumannovských - Martin Tichý (Slovo a Smysl)
This study examines a cluster of concepts that emerged in the critical writings of authors associated with the pre-war modernism of the 1910s (with a special focus on S. K. Neumann): the ‘civilizing’ of art, ‘civil art’, etc. demonstrates that such concepts were not primarily derived from a specific topic, but rather that they expressed the novelty of literary forms diverging at that time from contempo rary literary culture, under the influence of the changing reality of the modern world. Neumann’s concept of ‘civil art’ at the turn of the 1910s and 1920s can be understood as a programmatic idea that sought to situate modern art within a changing world, emphasizing experimentation based on indi vidual sensitivity. However, this idea was challenged by discussions on proletarian art, in the course of which the new concept of ‘civilism’ was introduced by the young avant-gardes of Devětsil (Karel Teige). This novel ‘ism’ was parasitic to ‘civil art’ and had a polemical purpose, enabling the young critics to distance themselves from pre-war modernism and its legacy, which they associated with ‘the old world’. When used in the context of literary history, we argue, the concept of ‘civilism’ can not be regarded as neutral, and any use of the term should reflect its origins in the discussion of the evolution of Czech literature during the era of the early avant-garde.